REFLEKSI PARIWISATA BERKELANJUTAN PADA SPA TERAPI BERBASIS KEMASYARAKATAN DI BALI - Komang Shanty Muni Parwati (Jurnal Ilmiah Hospitality Management, 2013)
The tourism industry is required to be creative because it involves many factors and segments in the society. It is particularly for continuing to grow and having a sustainable advantage that can be enjoyed by the local community. This study discusses spa-based community with examples of small-scale spa-businesses together, to be one source of employment in the industry of tourism. Spa as an example of creative efforts the local residents, contributing to the local community. The Community-based creative businesses, as an alternative to plunge women in the tourism industry. This study used a qualitative descriptive method. Spa as a center of health and beauty has enriching community-based health and beauty by linking tradition, culture, expertise, and creativity that already exists in the local community. It is essential for the advancement of culture, especially the tourism industry in Bali. To understand the importance of creativity and innovation in developing a spa business that reflects the local culture. Spa in addition to being one of the alternative forms of tourism, tourism pro-community, also is one form of sustainable tourism.